2001
DOI: 10.1177/0145482x0109500907
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Teachers of Visually Impaired Students via Distance Education: Perceptions of Teachers

Abstract: This study examined the perceptions of 12 students or graduates of a distance education training program in teaching students with visual impairments. Participants in the study discussed their experiences with courses delivered via interactive video, over the Internet, and by live instructors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, chronic shortages, especially in rural areas, spurred a move to distance education models, including the use of within-or across-state consortium agreements (DeMario & Heinze, 2001). Such programs have used combinations of Web-based instruction with interactive television and/or occasional face-to-face meetings in Colorado (Ferrell, Perschitte, Lowell, & Roberts, 2001), Michigan (Bruce & Hwang, 2001), California (Lueck, 2002), Utah (Day & Sebastian, 2002), Texas (Cooper & Keefe, 2001;Griffin-Shirely, Almon, & Kelley, 2002), and New York (Trief, Decker, & Ryan, 2004).…”
Section: Personnel Preparation In Vision Impairmentsmentioning
confidence: 99%
“…However, chronic shortages, especially in rural areas, spurred a move to distance education models, including the use of within-or across-state consortium agreements (DeMario & Heinze, 2001). Such programs have used combinations of Web-based instruction with interactive television and/or occasional face-to-face meetings in Colorado (Ferrell, Perschitte, Lowell, & Roberts, 2001), Michigan (Bruce & Hwang, 2001), California (Lueck, 2002), Utah (Day & Sebastian, 2002), Texas (Cooper & Keefe, 2001;Griffin-Shirely, Almon, & Kelley, 2002), and New York (Trief, Decker, & Ryan, 2004).…”
Section: Personnel Preparation In Vision Impairmentsmentioning
confidence: 99%
“…A study by McLinden et al (2006) examined problem-based learning in a distance education program for teachers of students with visual impairments. In another study, Cooper and Keefe (2001) described outcomes of distance education learning reported by 12 teachers, 10 of whom received certification to teach students with visual impairments through distance delivery. These 10 teachers reported general satisfaction with the program.…”
mentioning
confidence: 99%
“…The implementation of a distance learning model for preparing teachers of students with visual impairments is the direct result of a national shortage of such teachers and the limited accessibility of teacher preparation programs throughout the country (Cooper & Keefe, 2001). Although distance learning is not a new model of service delivery in the field of visual impairment, it is in a constant state of development and refinement as new technologies evolve.…”
mentioning
confidence: 99%